2008
DOI: 10.1007/s11258-008-9413-2
|View full text |Cite
|
Sign up to set email alerts
|

Complex vegetation responses to soil disturbances in mountain grassland

Abstract: We studied vegetation responses to disturbances originated by ants and voles in subalpine grasslands in the Eastern Pyrenees. We compared the effects of these small-scale disturbances with those of a large-scale disturbance caused by ploughing. We wanted to know if these soil disturbances promoted species richness through the existence of a specific guild of plants colonizing these areas, and if this guild was the same for all soil disturbances, independently of their extent. In general, grassland vegetation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Similar legume and non-legume forb species (Lotus corniculatus, Trifolium pratense, Myosotis sylvatica, and Ranunculus montanum) were found in both cattle-and sheep-grazed plots, in different proportions, as found by Sebastià et al (2008a). For a detailed description of vegetation, plant diversity, and soil at these grassland sites, see Sebastià (2004) and Sebastià and Puig (2008).…”
Section: Field Sites and Samplingsupporting
confidence: 56%
“…Similar legume and non-legume forb species (Lotus corniculatus, Trifolium pratense, Myosotis sylvatica, and Ranunculus montanum) were found in both cattle-and sheep-grazed plots, in different proportions, as found by Sebastià et al (2008a). For a detailed description of vegetation, plant diversity, and soil at these grassland sites, see Sebastià (2004) and Sebastià and Puig (2008).…”
Section: Field Sites and Samplingsupporting
confidence: 56%
“…The higher nutrient levels in ant mound soil are attributed to the accumulation of leaves, seeds, honeydew, feces, and corpses (Yu et al , ) in ant mound areas during ant mound building. Many studies have shown that nutrient enrichment can positively influence seedling establishment (King, ; Jones & Wagner, ; Sebastià & Puig, ). As a consequence, ant mounds may create nutrient‐rich patches and increase soil heterogeneity that further affects plant community structure and dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that, in less productive sites with a low plant canopy, limitation of light competition by disturbances by montane water voles should be less important. Achillea millefolium was also associated with highly disturbed plant communities, which is not surprising considering the fact that this species is typical of intensively grazed grasslands and well adapted to soil disturbances (Sebastià and Puig 2008).…”
Section: Differences In Plant Community Compositionmentioning
confidence: 79%
“…Contrary to our expectations and to findings of other studies (Questad and Foster 2007;Yoshihara et al 2009), the relative cover of ruderal species was not significantly higher in highly disturbed plant communities. The fact that earth tumuli might be quickly colonized by the neighbouring vegetation (Sebastià and Puig 2008), not allowing exogenous ruderal species to colonize the study site, could explain these results.…”
Section: Differences In Plant Community Compositionmentioning
confidence: 85%